Pedagogical strategies with technology in the teaching of university academic writing: a systematic review - Jara Conohuillca, Rossmery Jessica (2021)
Introduction. Writing academic texts is one of the most frequent and complex activities carried out at the university. For this reason, it is important to specify which are the pedagogical strategies and tools that teachers use to teach writing. Objective: A systematic investigation was carried out on the main research related to techno-pedagogical strategies. Method: In this case, 35 research articles on the topic itself and 17 additional articles were consulted to support the methodology and context of the article. Results: The analysis focused on pedagogical strategies such as collaborative work, autonomous learning, and competency-based learning. In addition, the tools most used by teachers were virtual environments such as blogs, word processors and virtual platforms. Discussion: On the other hand, it is important that teachers use virtual tools and environments according to the learning needs of their students.